GIS-Based Evaluation of The Integrated Waste Management Site in Sidodadi Village - Muh. Reza Al-Faridzi; Ade Mulawarman; Anggit Priadmodjo; Jafar Mukhlis; Ade Guna Saputra (Journal of Green Science and Technology, 2026)
This study evaluates the effectiveness of the Integrated Waste Management Facility (TPST) service in Sidodadi Sub-district, Wonomulyo District, Polewali Mandar Regency, using a spatial analysis approach based on the location–allocation method implemented in ArcGIS. The research is motivated by the high population density of Sidodadi, which has led to an increase in waste generation, while only a single TPST facility is currently operational. A quantitative descriptive method was applied, utilizing primary data from field observations and secondary spatial data, including building point data, road network data, and high-resolution satellite imagery. Spatial analysis was conducted by mapping waste generation at the building level, performing network-based distance analysis along the road network (as opposed to straight-line/Euclidean distance), and modeling TPST service coverage using a location– allocation model. The model parameters included a service distance cutoff of ≤ 1 km and facility capacity constraints based on the maximum number of households that can be served within a given facility. The results indicate that the existing TPST can serve approximately 600 households, corresponding to only about 15,84 % of the total residential buildings in Sidodadi Sub-district. Consequently, a significant proportion of densely populated residential areas remains outside the effective service coverage. This limited coverage is primarily influenced by insufficient facility capacity and service distances exceeding the defined cutoff. The study recommends the development of additional TPST facilities at strategically selected locations to increase service coverage percentage and enhance the efficiency and sustainability of waste management in Sidodadi Sub-district.